2019
DOI: 10.1177/1475921718811157
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and non-invasive surface crack detection for pressed-panel products based on online image processing

Abstract: Crack detection during the manufacturing process of pressed-panel products is an important aspect of quality management. Traditional approaches for crack detection of those products are subjective and expensive because they are usually performed by experienced human inspectors. Therefore, the development and implementation of an automated and accurate inspection system is required for the manufacturing process. In this article, a crack detection technique based on image processing is proposed that utilizes the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Below are some related works for concrete analysis that use image-processing techniques. Reference [21] described an online image-processing-based technique for rapidly and non-invasively detecting cracks in pressed-panel goods; however, this method used a standard camera, and the dataset was relatively small. An algorithm developed in [22] presented a feature detection approach that uses the Sobel operator to filter and denoise concrete images before implementing the Otsu method for thresholding segmentation for crack edge identification.…”
Section: Related Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Below are some related works for concrete analysis that use image-processing techniques. Reference [21] described an online image-processing-based technique for rapidly and non-invasively detecting cracks in pressed-panel goods; however, this method used a standard camera, and the dataset was relatively small. An algorithm developed in [22] presented a feature detection approach that uses the Sobel operator to filter and denoise concrete images before implementing the Otsu method for thresholding segmentation for crack edge identification.…”
Section: Related Implementationmentioning
confidence: 99%
“…Below are some related works for concrete analysis that use image-processing techniques. Reference [21] described an online image-processing-based technique for rapidly and non-invasively detecting cracks in pressed-panel goods; however, this method used a standard camera, and the dataset was relatively small. An algorithm developed in [22]…”
Section: Related Implementationmentioning
confidence: 99%
“…To overcome these issues, researchers have applied different techniques for eliminating the effect of varying conditions. 2427 Fujita and Hamamoto 28 used a median filter to remove shadings from concrete surface images and a line filter with Hessian matrix to enhance cracks and then used probabilistic relaxation for crack detection. Iyer and Sinha 25 found that cracks in pipe images are darkest in the images, locally linear, and have tree-like geometry.…”
Section: Related Workmentioning
confidence: 99%
“…Domestic and foreign scholars have achieved fruitful results on image processing of ecommerce products [8][9][10]. To extract the exact text information in ecommerce images, Wasim et al…”
Section: Introductionmentioning
confidence: 99%